2023
DOI: 10.1093/hr/uhad036
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic and metabolic investigations disclose the factors that lead to skin cracking in chili-type pepper fruit varieties

Abstract: The hydrophobic cuticle encasing the fruit skin surface plays critical roles during fruit development and post-harvest. Skin failure often results in the fruit surface cracking and forming a wound-periderm tissue made of suberin and lignin. The factors that make the fruit skin susceptible to cracking have yet to be fully understood. Herein, we investigated two varieties of chili peppers (Capsicum annuum L.), Numex Garnet, whose fruit has intact skin, and Vezena Slatka, whose fruit has cracked skin. Microscopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 91 publications
0
1
0
Order By: Relevance
“…In previous studies, it was found that the roughness and cracking of the pericarp are correlated with lignin content. When the pericarp cracks, water loss becomes severe, leading to a shorter fruit lifespan [49]. The skin of potato tubers serves as the primary barrier for water retention.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, it was found that the roughness and cracking of the pericarp are correlated with lignin content. When the pericarp cracks, water loss becomes severe, leading to a shorter fruit lifespan [49]. The skin of potato tubers serves as the primary barrier for water retention.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, targeted carotenoid metabolomics using saponification has the potential to expand our knowledge of specific classes of carotenoid metabolites contributing to color expression. Additionally, non-targeted metabolomics can help to identify a broader spectrum of metabolic products and understand their metabolism in relation to fruit color development ( Luo et al., 2022 ; Marinov et al., 2023 ). Until now, such comprehensive saponification-assisted targeted carotenoid metabolomics and non-targeted secondary metabolomics studies on pepper fruit color development have not been reported.…”
Section: Introductionmentioning
confidence: 99%